Gay and lesbian aging : research and future directions - Herdt, Gilbert H., 1949-; De Vries, B. (Brian) (Springer Pub. Co., 2004)
Annotation The year 2003 marked the 30th anniversary of the landmark "declassification" of homosexuality as a disease by the American Psychiatric Association-a watershed in the lives of gays and lesbians in the United States. For the first time in history, a generation of self-identified lesbians, gay men, bisexuals, and transgender individuals are approaching retirement. This volume brings to the forefront important issues concerning the health, mental health, and concomitant special social service needs of the gay and lesbian population and emphasizes the need for more research on aging sexual minorities